2011
DOI: 10.1002/aic.12726
|View full text |Cite
|
Sign up to set email alerts
|

Metastable boundary conditions of water‐in‐oil emulsions in the hydrate formation region

Abstract: A stepwise pressurization method was proposed for determining the metastable boundary conditions of water-in-oil emulsions in the hydrate formation region. The metastable boundary pressures of four water-in-n-octane emulsions in the presence of methane gas were determined at four specified temperatures. The experimental results show that the metastable boundary pressures increase with decreasing water droplet sizes. A thermodynamic model was developed for calculating the metastable boundary conditions of a wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
1
15
1
1
Order By: Relevance
“…Therefore, to facilitate the above applications, the growth kinetics of gas hydrates needs to be properly investigated and modeled . When hydrates appear in oil and gas production pipelines, water are typically dispersed in the oil phase forming water‐in‐oil emulsions due to the usual presence of resin and asphaltene and flow turbulence. Conversely, solid‐phase kinetics involved in gas hydrate formation is slow and somehow limited current application of hydrate technology .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to facilitate the above applications, the growth kinetics of gas hydrates needs to be properly investigated and modeled . When hydrates appear in oil and gas production pipelines, water are typically dispersed in the oil phase forming water‐in‐oil emulsions due to the usual presence of resin and asphaltene and flow turbulence. Conversely, solid‐phase kinetics involved in gas hydrate formation is slow and somehow limited current application of hydrate technology .…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that no hydrate forms during the experimental process for measuring the gas solubility, the experimental pressure should be lower than the equilibrium pressure value at the current temperature of 277.2 K. For a pure water environment, the phase equilibrium pressure of feed gas under 277.2 K is 1.36 MPa, according to the two-step hydrate formation mechanism [27]. The hydrate equilibrium pressure for emulsion systems is close to that of pure water system, although there exist higher metastable boundary conditions in water-in-oil emulsions [14]. The solubility results and the corresponding experimental conditions are listed in Table 2.…”
Section: Gas Solubility In Emulsionmentioning
confidence: 99%
“…The hydrate formation in emulsions is related to the magnitude of the subcooling. Chen et al [14] determined the metastable boundary conditions of water-in-oil emulsions in the methane hydrate formation region using a stepwise pressurization method. The experimental results showed that the metastable boundary pressures increase with decreasing water-droplet sizes, but when the system pressure exceeds the metastable boundary pressure, hydrate formation occurs and the metastable state of the emulsion collapses.…”
Section: Introductionmentioning
confidence: 99%
“…在此基础上, 诸多研究者 [14,15] 通过对水 在水合物相中的化学势及Langmuir常数计算的改进, 进一步丰富与加强了基于统计热力学的水合物生成 模型. Chen等人 [16] 则通过将水合物的热力学计算和 一般的溶解热力学计算统一, 提出了双过程水合物 生成预测模型, 该模型所需输入参数简单, 计算稳定 性好, 且可应用于含极性抑制剂 [17] 、 含盐 [18] 和油水分 散体系 [19] 的水合物生成预测. 此外, 工程领域应用 性较为广泛的处理含水合物复杂体系的热力学预测 软件, 包括: 由科罗拉多矿业大学提出的基于Gibbs 自由能最小所建立的含水合物复杂体系热力学平衡 计算软件CSMGem [20] , 以及赫瑞-瓦特大学提出的基 于vdW-P及Kihara模型计算水合物生成热力学平衡的 软件HydFACT [21] .…”
Section: 水合物生成热力学理论 源于20世纪50年代末unclassified